Effect of Bacterial Nanocellulose with Chemisorbed Antiseptics on Alveolar Bone Repair in Rats Undergoing Bisphosphonate Therapy - Marcelo Matos Rocha; Valesca Sander Koth; Marcela Wiltgen Jeffman; Fernanda Gonçalves Salum; Josiane de Almeida; Karina Cesca; Karen Cherubini (Pharmaceutics)
Objectives: This work investigated the effect of bacterial nanocellulose (BNC) alone or with chemisorbed chlorhexidine or povidone-iodine on post-tooth extraction repair in rats undergoing bisphosphonate therapy. Methods: Forty Wistar rats were treated with zoledronic acid, subjected to tooth extractions and allocated into groups according to the material inserted in the post-extraction socket: (1) BNC (n = 10); (2) BNC/Iodine (n = 10); (3) BNC/Chlorhex (n = 10); (4) Control (n = 10). Maxillae were dissected and macro- and microscopically analyzed. Results: Oral lesion frequency on macroscopic examination did not differ between the groups, whereas it was larger in the BNC/Iodine group compared to the BNC/Chlorhex and Control. BNC/Chlorhex had significantly more connective tissue than did BNC but did not differ from the BNC/Iodine and Control. Epithelium, vital bone, non-vital bone, tooth fragment and inflammatory infiltrate did not significantly differ between the groups. BNC/Iodine showed greater CD31 immunostaining compared to BNC and the Control. Myeloperoxidase staining did not differ between the groups, and scanning electron microscopy analysis showed similar characteristics in all groups. Conclusions: BNC with chemisorbed povidone-iodine is associated with increased vascularization in post-extraction wounds of rats undergoing bisphosphonate therapy, whereas BNC with chemisorbed chlorhexidine improves connective tissue formation. BNC works as an effective carrier for the antiseptics tested.